Unilateral Perforant Path Transection Does Not Alter Lateral Entorhinal Cortical or Hippocampal CA3 Arc Expression - Cooper, Tara L.; Thompson, John J.; Turner, Sean M.; Watson, Cory; Lubke, Katelyn N.; Logan, Carly N.; Maurer, Andrew P.; Burke, Sara N. (Frontiers in Systems Neuroscience, 2022)
It is well established that degradation of perforant path fibers is associated with age-related cognitive dysfunction and CA3 hyperactivity. Whether this fiber loss triggers a cascade of other functional changes within the hippocampus circuit has not been causatively established, however. Thus, the current study evaluated the effect of perforant path fiber loss on neuronal activity in CA3 and layer II of the lateral entorhinal cortex (LEC) in relation to mnemonic similarity task performance. Expression of the immediate early gene Arc was quantified in rats that received a unilateral right hemisphere transection of the perforant path or sham surgery that cut the cortex but left the fibers intact. Behavior-related expression of Arc mRNA was measured to test the hypothesis that fiber loss leads to elevated activation of CA3 and LEC neurons, as previously observed in aged rats that were impaired on the mnemonic similarity task. Transection of perforant path fibers, which has previously been shown to lead to a decline in mnemonic similarity task performance, did not alter Arc expression. Arc expression in CA3, however, was correlated with task performance on the more difficult discrimination trials across both surgical groups. These observations further support a link between CA3 activity and mnemonic similarity task performance but suggest the reduced input from the entorhinal cortex to the hippocampus, as observed in old age, does not causatively elevate CA3 activity.